Combined Administration of Vitamin D3 and Geniposide Is Less Effective than Single Use of Vitamin D3 or Geniposide in the Treatment of Ulcerative Colitis - Lu, Yingyu; Chen, Jianqiang; He, Xueling; Xu, Shuoxi; Chen, Yong-er; Gao, Jie; Hou, Shaozhen (Frontiers in Pharmacology, 2021)
With the increasing incidence of ulcerative colitis (UC) in China, Chinese medicinal herbs or relatively active compounds are widely applied in treating UC and may be combined with other therapeutic agents such as vitamin D3. Nevertheless, the efficacy of these combinations for UC is unclear. Geniposide, an active component in many Chinese herbal medicines, could ameliorate dextran sulfate sodium (DSS)-induced colitis in mice. This study was designed to determine the efficacy and mechanism of the single use and combination of geniposide and vitamin D3 on a mouse model of acute colitis. The data showed that a single administration of geniposide (2 mg/kg) or vitamin D3 (4 IU/day) could significantly improve the symptoms of UC and relieve colon damage. However, the combined treatment of geniposide (2 mg/kg) and vitamin D3 (4 IU/day) exerted less beneficial effects on UC in mice, indicating by less improvement of UC symptoms, colon damage and inflammatory infiltration. Our data further demonstrated that geniposide could inhibit the activation of p38 MAPK and then restrict the vitamin D receptor signaling stimulated by vitamin D3. These results implied that the combination of geniposide and vitamin D3 might not be an ideal combined treatment for acute colitis, and the combination of vitamin D supplementary and geniposide (or herbal medicines rich in geniposide) need more evaluation before being applied to treat UC in clinic.